Orthodontic Management of Anterior and Unilateral Posterior Crossbite: A Case Report - Chaudhary, Nabin Kumar (Journal of Karnali Academy of Health Sciences, 2023)
Crossbite refers to abnormal labiolingual and buccolingual relations between the opposing teeth. This results in the imbalanced facial appearance of the patient causing varied degrees of distress based on the individual’s values and self-esteem. The management of skeletal class III malocclusion with anterior and posterior crossbite can be challenging. This case report describes a case of skeletal class III malocclusion complicated with an anterior, and unilateral posterior crossbite, and severe crowding which was managed satisfactorily with a fixed orthodontic appliance. The proper clinical examination, diagnosis, problem list, and formulation of the treatment plan are of utmost importance for the proper management of the case. The diagnosis can be done through proper history, clinical examination, an orthopantomogram, and a lateral cephalogram. The patient’s grin was transformed from a non-consonant to a consonant smile, and the profile was transformed from slightly concave to straight.